19 PENGARUH BOOK VALUE, DEBT TO EQUITY RATIO, DEBT TO ASSET RATIO, RETURN ON ASSET TERHADAP HARGA SAHAM PADA SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSAEFEK INDONESIA PERIODE 2011-2013. - DIANA SARI (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
Investing in the capital market is an alternative for investors in investing, but investing in stocks is quite risky even though it has substantial profits. Share prices are influenced by the condition of the company, many factors affect the condition of the company, including fundamental factors such as EPS, PER, BVS, PBV, ROE. From several factors, investors prefer BV, DER, DAR, and ROA in predicting future stock prices. These four factors are the most important ones seen by investors in making investment decisions. because it can estimate the continuation of the company and the net profit to get. The purpose of this study was to determine the effect of Book Value, Debt To Equity, Ratio, Debt To Asset Ratio, Return on Assets on mining sector stock prices in the period from 2011 to 2013. The population in this study were 51 mining sector companies listed in IDX for the period 2011-2013. In sampling, the method used was purposive sampling so that the sampling conducted was 17 mining sector companies. The data analysis technique used is multiple linear regression. The results show that the variables BV and ROA are partially significant to the stock price while DER and DAR have no significant effect on stock prices. Simultaneously significant variables of BV, DER, DAR, and ROA on the stock price in the mining sector during the IDX period from 2011 to 2013